SOLAR POWER PLANT PLANNING FOR HOUSEHOLD SCALE BY THE AID PVSYST PROGRAM - Layarda, Beny (Faculty of Engineering, Universitas Tanjungpura, 2024)
Geographically, Indonesia is located on the equator, so it is very rich in solar energy sources with an average solar radiation intensity of around 4.8 kWh/m2 per day throughout Indonesia. The main component contained in solar power plants is solar cells which function to convert sunlight into electrical energy This research discusses the Planning of Solar Power Plants for Household Scale Assisted by the PVsyst Program. The purpose of this research is to determine how many solar modules, batteries, solar charger controllers, and inverters are needed for planning solar power plants in households with 900 VA and 1300 VA power. Based on manual calculations and simulations of the PVsyst program, 10 Luxor Ecoline Half Cell 280 Wp polycrystalline modules, 12 Narada EosG 2000 Ah batteries, 1 Victron Energy Mppt 250/100 solar charge controller, and 1 Victron Multiplus Compact 24/1200/25 inverter. The capacity of the solar power plant components for 900 VA and 1300 VA household loads is approximately the same, this is because the average daily energy usage is only slightly different. In 900 VA households, the number of occupants of 6 people uses 7088 Wh/day of energy, while in 1300 VA households with 4 occupants uses 7274.5 Wh/day of energy.